Análisis a los estados financieros y propuesta de mejoras a la Cooperativa de Ahorro y Crédito CACPE – CELICA, periodo 2016 - 2017 - Vivanco Jumbo, Amalia Isolina (2019)
The present thesis entitled: "Analysis of the financial statements and proposal for improvements to the CACPE - CELICA Savings and Credit Cooperative, 2016 - 2017 period", was developed with the purpose of fulfilling the general objective. It allows to identify the real economic-financial situation of the entity and thus contribute to the correct decision making regarding the administration of its monetary resources and thus improve the current situation of the financial institution. The methodology applied in the preparation of the financial analysis begins with the compilation of the necessary information for its development. Subsequently, the specific objectives were met, starting with a vertical analysis of the financial situation and the 2017 income statement, with the purpose of measuring the degree of representativeness of each account vis-à-vis the group to which it belongs, where it was determined that the assets are composed mainly of 61.37% in credit portfolio, 70.65% liabilities in obligations with the public and equity by the share capital corresponding to 18.10%. All this is considered an appropriate financial structure. While in income the account with greater relevance was interest and discounts of credit portfolio with 92.27% of total income and in expenses is interest caused by obligations with the public in 49.12% of total income, providing surplus and at the same time this strengthens the institutional capital of the cooperative. The horizontal analysis was also carried out to identify the variations existing between 2016 and 2017, obtaining as a result a minimum growth of assets specifically in available funds increased by 20.58% and decreased the -0.30% of credit portfolio, while liabilities increased obligations to the public by 7,91% which is good for the institution since these resources are used in the placement of credits and equity, the contribution of partners increased by 4.87% for the entry of new partners, while income increased by 3.25% and expenditure by 0.55% generating a surplus at the end of the year. Subsequently in the application of the indicators of the PERLAS Monitoring System, it is evident that the cooperative has positive aspects such as: high collection of fixed-term deposits which allows it to use a minimum percentage of external financing for the placement of credits, while the negative aspects consist of the following: excess liquidity, low margin of profitability, slow growth of members and the default of loans exceeds the established goal. Finally, once the financial analysis was carried out, the weaknesses of the cooperative were identified and solutions were proposed through the proposal of improvements. Also attached is the report for consideration by the directors of the entity with the purpose of being taken into account and therefore obtain better results in the future.